Bismuth-containing drugs in clinical practice in the XXI century - history or a new round of possibilities? - V. A. Akhmedov (Лечащий Врач, 2024)
Background. Bismuth is a somewhat rare element, similar in content to silver and mercury, but cheaper to produce because large amounts of bismuth are extracted as a by-product of copper and tin processing. Bismuth and its compounds are considered moderately safe and relatively non-toxic. The relatively low toxicity of bismuth compounds is mainly due to their insolubility in nearly neutral aqueous solutions, such as biological fluids. In addition, most bismuth compounds have been demonstrated to be less toxic than even sodium chloride.Objective. The aim of the article – to outline the feasibility of clinical use of bismuth preparations in the XXI century. Despite many years of using bismuth preparations in clinical practice, the relevance of their use does not weaken, but on the contrary, new niches for its use in clinical practice are opening up. In addition to the well-known cytoprotective effect, the bismuth preparation serves as a worthy alternative to standard triple therapy in the form of quadruple therapy with bismuth preparations, the main one of which is currently bismuth tripotassium dicitrate, which is reflected in the recommendations of the Russian Gastroenterological Association and the Endoscopic Society RENDO. The high efficiency of the possibility of combining bismuth tripotassium dicitrate not only with tetracycline, but also with other antibiotics is shown. The addition of bismuth tripotassium dicitrate to triple regimens containing clarithromycin, levofloxacin, metronidazole allows to increase the effectiveness of eradication by more than 92% with a 14-day course of use. Important bonuses of clinical application of bismuth tripotassium dicitrate are absence of resistance development during its application, combination of bactericidal and cytoprotective effects, as well as good tolerability. Currently, new antibacterial properties of bismuth tripotassium dicitrate are being discovered for treatment of other pathogens, besides Helicobacter pylori. One of worthy representatives of bismuth tripotassium dicitrate is Russian mediication based on bismuth tripotassium dicitrate, which has improved profile of antibacterial activity and safety.